The role of reproductive hormones in postpartum depression - Schiller, Crystal Edler; Meltzer-Brody, Samantha; Rubinow, David R. (CNS spectrums, 2015)
Despite decades of research aimed at identifying the causes of postpartum depression (PPD), PPD remains common, and the causes are poorly understood. Many have attributed the onset of PPD to the rapid perinatal change in reproductive hormones. Although a number of human and nonhuman animal studies support the role of reproductive hormones in PPD, several studies have failed to detect an association between hormone concentrations and PPD. The purpose of this review is to examine the hypothesis that fluctuations in reproductive hormone levels during pregnancy and the postpartum period trigger PPD in susceptible women. We discuss and integrate the literature on animal models of PPD and human studies of reproductive hormones and PPD. We also discuss alternative biological models of PPD to demonstrate the potential for multiple PPD phenotypes and to describe the complex interplay of changing reproductive hormones and alterations in thyroid function, immune function, hypothalamic–pituitary–adrenal (HPA) axis function, lactogenic hormones, and genetic expression that may contribute to affective dysfunction. There are 3 primary lines of inquiry that have addressed the role of reproductive hormones in PPD: nonhuman animal studies, correlational studies of postpartum hormone levels and mood symptoms, and hormone manipulation studies. Reproductive hormones influence virtually every biological system implicated in PPD, and a subgroup of women seem to be particularly sensitive to the effects of perinatal changes in hormone levels. We propose that these women constitute a “hormone-sensitive” PPD phenotype, which should be studied independent of other PPD phenotypes to identify underlying pathophysiology and develop novel treatment targets.